The Influence of Work-Life Balance and Transformational Leadership on Employee Performance in Teleworking Environment - Emmanuel Kevin Gunawan; Esther Tirza Suzanti Kalalo; Gebrina Oktaviani Tarigan; Abdul Rohman (Jurnal Entrepreneur dan Entrepreneurship, 2024)
During the pandemic era, the teleworking policy had to be implemented, but afterward, this policy was still being implemented. The aim of this study is to investigate the influence of work-life balance and transformational leadership on employee performance in a teleworking environment. Quantitative research method was used and the primary data were obtained from distributed questionnaires. The research was conducted on 150 employees in companies that implement teleworking. Data were analyzed using the SEM model. The results of this study shows that transformational leadership and work-life balance have a significant and positive effect on employee performance, either directly or through job satisfaction.